2006
DOI: 10.1590/s0370-44672006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da condutividade hidráulica em área de recarga do aqüífero Botucatu

Abstract: O trabalho apresenta os valores de condutividade hidráulica obtidos a partir de ensaios de infiltração realizados na bacia do Córrego Vaçununga, na região de Luis Antônio (nordeste do Estado de São Paulo). Os ensaios foram realizados em arenitos da Formação Botucatu que apresentam características típicas das áreas de recargas do aqüífero livre Botucatu. Além dos ensaios de duplo anel, foram realizados ensaios em laboratório para caracterizar os materiais inconsolidados quanto aos índices físicos. Os resultados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
4
3
0
1
Order By: Relevance
“…The soil has a low CEC (maximum value 4.20 cmolc Kg -1 ) and it suggests a low capacity to adsorb cations by electrostatic adsorption (Fagundes & Zuquette, 2011). Mean soil properties presented values in accordance with the typical characteristics of the studied soil (Giacheti et al, 1993;Zuquette & Palma, 2006), and are shown in Table1.…”
Section: Soil Properties Statistical Analysissupporting
confidence: 67%
“…The soil has a low CEC (maximum value 4.20 cmolc Kg -1 ) and it suggests a low capacity to adsorb cations by electrostatic adsorption (Fagundes & Zuquette, 2011). Mean soil properties presented values in accordance with the typical characteristics of the studied soil (Giacheti et al, 1993;Zuquette & Palma, 2006), and are shown in Table1.…”
Section: Soil Properties Statistical Analysissupporting
confidence: 67%
“…We also obtained a low CEC of 4.20 cmolc Kg -1 , indicative of a soil with low capacity to adsorb cations by electrostatic adsorption (Fagundes & Zuquette, 2011). Finally, the mean values of the soil physical properties were in accordance with typical values found earlier in this type of soil Zuquette & Palma, 2006 Fig. 3.11 is a zoom in Fig.…”
Section: Double-ring Infiltrometer (Dri)supporting
confidence: 88%
“…The soil has a low CEC (maximum value 4.20 cmolc Kg -1 ) and it suggests a low capacity to adsorb cations by electrostatic adsorption (Fagundes & Zuquette, 2011). Mean soil properties presented values in accordance with the typical characteristics of the studied soil Zuquette & Palma, 2006). …”
Section: Average Soil Propertiessupporting
confidence: 66%
“…The soil has a low CEC (maximum value 4.20 cmolc Kg -1 ) and it suggests a low capacity to adsorb cations by electrostatic adsorption (Fagundes & Zuquette, 2011). Mean soil properties presented values in accordance with the typical characteristics of the studied soil (Giacheti et al, 1993;Zuquette & Palma, 2006). …”
Section: Average Soil Propertiessupporting
confidence: 65%